Comparison of Visual Field Progression Rate before and after Cataract Surgery in Patients with Open-Angle and Angle-Closure Glaucoma. (22nd June 2021) - Su, Wei-Wen; Hsieh, Shian-Sen; Sun, Ming-Hui; Chen, Henry Shen-Lih; Lee, Yung-Sung; Yang, Lan-Yan; Tseng, Hsiao-Jung
Abstract : Purpose . To evaluate Humphrey visual field (VF) progression rate before and after cataract surgery in patients with open-angle glaucoma (OAG) and angle-closure glaucoma (ACG). Methods . After reviewing all records in our Humphrey VF database from July 1, 2001, to December 31, 2018, eyes of OAG and ACG that had received uncomplicated phacoemulsification with intraocular lens implantation during the period and had been followed up regularly for more than one year with ≥3 reliable VF tests before and after cataract surgery, respectively, were enrolled. The VF progression rate, visual acuity, and intraocular pressure (IOP) before and after cataract surgery were compared. Results . Seventy-seven eyes (OAG: 51; ACG: 26) from 60 patients were enrolled. The mean preoperative and postoperative follow-up durations were 4.89 ± 2.70 and 5.48 ± 2.30 years in the OAG group and 5.14 ± 3.31 and 5.97 ± 2.35 years in the ACG group. IOP and visual acuity significantly improved postoperatively in both groups. In the OAG group, there was no significant change in the VF progression rate (pre-op: −0.39 ± 0.94 dB/year; post-op: −0.47 ± 0.72 dB/year) (P = 0.619 ), whereas, in the ACG group, the rate significantly flattened after surgery from −1.39 ± 1.31 dB/year to −0.34 ± 0.64 dB/year (P = 0.003 ). Conclusions . The VF progression rate did not differ between preoperative and postoperative eyes with OAG, but those with ACG exhibited rapid VF decline preoperatively, which was significantly flattened postoperatively.